A Life-Changing Moment in a Patient with Type 1 Diabetes: Insulin Holiday: - Butt, Muhammad Imran; Mukhtar, Noha; Riazuddin, Muhammad; Amer, Lama; Elsayed, Tarek (Galen Medical Journal, 2020)
Background: The diagnosis of type 1 diabetes can be a life-changing moment for our patients particularly having to live with the idea of taking insulin all their life and the barriers it can bring about. Case report: We report a patient with ten years of autoimmune type 1 diabetes treated with insulin. He was able to stop insulin in favour of oral diabetes agents after dynamic endocrine tests confirmed micro insulin secretion despite autoimmunity. Our case demonstrates that a detailed history and thorough investigations adopting a holistic approach can sometimes change the course of disease management and can leave a positive impact on the life of our patients. Conclusion: Patients with partial retention of beta-cell function in type 1 diabetes can temporarily stop insulin safely with ongoing surveillance. [GMJ.2020;9:e1769]